Seismogenic sources in the bay of bengal vis-a-vis potential for tsunami generation and its impact in the northern Bay of Bengal coast - Khan, A.A. (Springer, 2012)
Geodynamic status, seismo-tectonic environment, and geophysical signatures of the Bay of Bengal do not support the occurrence of seismogenic tsunami. Since thrust fault and its intensity and magnitude of rupture are the key tectonic elements of tsunamigenic seismic sources, the study reveals that such characteristics of fault-rupture and seismic sources do not occur in most of the Bay of Bengal except a small segment in the Andaman–Nicobar subduction zone. The inferred segment of the Andaman–Nicobar subduction zone is considered for generating a model of the deformation field arising from fluid-driven source. The model suggests local tsunami with insignificant inundation potential along the coast of northern Bay of Bengal. The bathymetric profile and the sea floor configuration of the northern Bay of Bengal play an important role in flattening the waveform through defocusing process. The direction of motion of the Indian plate makes an angle of about 30 with the direction of the opening of Andaman Sea. The opening of Andaman Sea and the direction of plate motion of the Indian plate results in the formation of Andaman trench where the subducting plate dives more obliquely than that in the Sunda trench in the south. The oblique subduction reduces significantly the possibilities of dominant thrust faulting in the Andaman subduction zone. Further, north of Andaman subduction in the Bengal–Arakan coast, there is no active subduction. On the otherhand, much greater volume of sediments (in excess of 20 km) in the Bengal–Arakan segment reduces the possibilities of mega rupture of the ocean floor. The water depth (&1,000 m) along most of the northern Bay of Bengal plate margin is not optimum for any significant tsunami generation. Hence, very weak possibility of any significant tsunami is suggested that based on the interpretation of geodynamic status, seismo-tectonic environment, and geophysical signatures of the Andaman subduction zone and the Bengal–Arakan coast.